Rozsnyai Japán nyelvmestere - Albeker, András Zsigmond (Távol-keleti Tanulmányok, 2017)
In Hungary, as the 15th volume of self-study series “Rozsnyai gyors nyelvmesterei” (“Rozsnyai’s Foreign language speed master series”), the Rozsnyai publishing company has published “Japán / Japanische Grammatik” at 1905. This book was the first Japanese textbook written in Hungarian. The purpose of this paper is an attempt to define the author of “Speed master Japanese”, and reference materials the author used to write this textbook. As a result of bibliographical research, we know that the author was Akantisz Viktor, who studied philosophy and law at the Budapest University, and after graduation made a living as a translator, writer, painter, illustrator and book-restorer. At the present stage of research, we were unable to get any information about wether he visited to Japan or not, and where he studied Japanese language. When Akantisz wrote this textbook, he used the materials of the German philologist, August Seidel. Although there are many mistakes and imperfect explanations in this textbook, as the first Japanese textbook in Hungarian, it contains valuable material.